A novel serum protein biomarker for the late-stage diagnosis of nasopharyngeal carcinoma - Yi-Xi Pan; Qi Huang; Shan Xing; Qian-Ying Zhu (BMC Cancer)
Abstract Background Nasopharyngeal carcinoma (NPC) is a malignant tumor prevalent in Southern China, strongly associated with Epstein-Barr virus (EBV) infection. Accurate diagnosis is critical in determining treatment strategies for NPC. In clinical practice, imaging techniques are the most predominant diagnostic methods, which are costly and may fail to detect small metastatic lesions. Moreover, while EBV antibody and DNA tests contribute to the assessment of tumor progression, they carry the risk of false negatives. Methods To develop novel serum protein biomarkers for late-stage NPC diagnosis, our study included 189 samples, including healthy controls (HCs) and early- or late-stage NPC patients. A high-throughput serum proteomics approach was employed to delineate protein profiles, followed by enzyme-linked immunosorbent assay (ELISA) validation of candidate biomarkers. Results Our study identified fibronectin 1 (FN1) as a promising serum biomarker for late-stage NPC. The serum levels of FN1 significantly decreased with tumor progression, achieving AUCs of 0.71 and 0.72 in differentiating late-stage NPC patients from HCs and early-stage NPC patients, respectively. Importantly, FN1 demonstrated diagnostic utility in challenging cases, accurately identifying all VCA-IgA-negative and 88.2% EBV DNA-negative patients with late-stage NPC. Combining FN1 with VCA-IgA or EBV DNA test significantly increased diagnostic sensitivity for advanced NPC. Conclusions Our discovery of FN1 as a biomarker for the late-stage diagnosis of NPC will assist in clinical treatment decisions and improve the prognosis of patients.